2019
DOI: 10.1002/cam4.2584
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0028502 and hsa_circ_0076251 are potential novel biomarkers for hepatocellular carcinoma

Abstract: Circular RNAs (circRNAs) have been increasingly revealed to be desirable biomarkers for some tumors, including hepatocellular carcinoma (HCC). Combined with our previous microarray screening results, we aimed to determine the hsa_circ_0028502 and hsa_circ_0076251 expression features in HCC, analyze the relationship between their expression level and clinical and pathological characteristics, and investigate their diagnostic and prognostic values. Our data demonstrated that the hsa_circ_0028502 and hsa_circ_007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…As a biomarker of cancer, many circRNAs have been proved to be related to the clinical and pathological characteristics of cancer, which can provide theoretical support for the functional studies of circRNAs. 29 Therefore, the research on circ_0058124 still needed us to enrich. Our study focused on the effect of circ_0058124 on TC cell proliferation, metastasis and metabolic abilities, but the expression of related proteins was not detected, which was also the shortcoming of our experimental design, so further exploration was needed in the follow-up experiments.…”
Section: Discussionmentioning
confidence: 99%
“…As a biomarker of cancer, many circRNAs have been proved to be related to the clinical and pathological characteristics of cancer, which can provide theoretical support for the functional studies of circRNAs. 29 Therefore, the research on circ_0058124 still needed us to enrich. Our study focused on the effect of circ_0058124 on TC cell proliferation, metastasis and metabolic abilities, but the expression of related proteins was not detected, which was also the shortcoming of our experimental design, so further exploration was needed in the follow-up experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies performed on HCC patients have shown that hsa_circ_0000798 [174] hsa_circ_0027089 [175] and hsa_circ_0058124 [176] are upregulated in HCC tissues, whereas some circRNAs are downregulated, including hsa_circSMARCA5 [177] hsa_circ_0068669 [178] hsa_circ_0028502 [179] and hsa_circ_0076251 [179] . These circRNAs are supposed to serve as potential biomarkers for HCC.…”
Section: Circrnas Are Promising Biomarkers In Cancermentioning
confidence: 99%
“…These characteristics endow circRNAs with many potential functions, such as acting as a microRNA (miRNA) sponge, or combining with proteins to form RNA-protein complexes to modulate the function of proteins (6). Accumulating research has demonstrated that circRNAs are related to the pathogenesis of tumors (7)(8)(9)(10). Importantly, circRNA can function as competitive endogenous RNA (ceRNA) to regulate the expression level of miRNAs and target genes (6).…”
Section: Introductionmentioning
confidence: 99%